Javascript data structures and algorithms : an introduction to understanding and implementing core data structure and algorithm fundamentals - Bae, Sammie (New York : Apress, 2022)
Explore data structures and algorithm concepts and their relation to everyday JavaScript development. A basic understanding of these ideas is essential to any JavaScript developer wishing to analyze and build great software solutions. You'll discover how to implement data structures such as hash tables, linked lists, stacks, queues, trees, and graphs. You'll also learn how a URL shortener, such as bit.ly, is developed and what is happening to the data as a PDF is uploaded to a webpage. This book covers the practical applications of data structures and algorithms to encryption, searching, sorting, and pattern matching. It is crucial for JavaScript developers to understand how data structures work and how to design algorithms. This book and the accompanying code provide that essential foundation for doing so. With JavaScript Data Structures and Algorithms you can start developing your knowledge and applying it to your JavaScript projects today.
1. Big-O Notation -- 2. JavaScript: Unique Parts -- 3. JavaScript Numbers -- 4. JavaScript Strings -- 5. JavaScript Arrays -- 6. JavaScript Objects -- 7. JavaScript Memory Management -- 8. Recursion -- 9. Sets -- 10. Searching and Sorting -- 11. Hash Tables -- 12. Stacks and Queues -- 13. Linked Lists -- 14. Caching -- 15. Trees -- 16. Heaps -- 17. Graphs -- 18. Advanced Strings -- 19. Dynamic Programming -- 20. Bit Manipulation.
Description based on publisher-supplied MARC data.
Keywords: Javascript: unique parts; Javascript arrays; Searching and sorting